PENGGUNAAN MEDIA FLASHCARD UNTUK MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KREATIF - Sumantri, Nanda Handayani; Kurnia, Dadang; Djuanda, Dadan (Jurnal Pena Ilmiah, 2019)
The purpose of this research to see representation of upgrading earning outcome dan creative thinking skills in social studies use the flashcard.Â  It was done in Mulyasari elementary school. This research was an action research using Kemmis adn Mc. Taggart design which in its implementation give some repaired to fix the problems. The seubject were students of class IV. The target of this research is 80% for earning outcome according to KKM and 80% for creative thinking skills. This research was done of theree cycle. In cycle III, the percentage of theÂ  teacher performance in planning and implementing earning is 100%, the percentage of the student passed the standard of achievement while the other is 82,002, and the percentage of creative thinking skills is 87,1%. Based on these results it can be concluded there is upgrading for earning outcome and creative thinking skills on earning to use flashcard.